The internal locus of control and financial management behavior - Meylandariska; Abel Tasman (Operations Management and Information System Studies, 2022)
This study aims to measure the effect of financial literacy, financial self-efficacy and financial attitude on financial management behavior with an internal locus of control as a moderating variable in gen Z students at the Faculty of Economics, Padang State University with a sample of 190 respondents. Sampling was carried out using the Probability Sampling technique with the proportional random sampling method. The criteria used are active students for the 2021/2022 academic year. Data analysis using SEM-PLS with the SmartPLS 3 application. The results showed that financial literacy did not have a significant effect on the financial management behavior of Gen Z of students, financial self-efficacy had a negative and significant effect on the financial management behavior of Gen Z students and financial attitude had an influence which positive and significant to the financial management behavior Gen Z students. Locus of control cannot moderate the relationship between financial literacy, financial self-efficacy and financial attitude on financial management behavior.